1997
DOI: 10.1105/tpc.9.3.425
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis NIM1 protein shows homology to the mammalian transcription factor inhibitor I kappa B.

Abstract: The NlM7 (for noninducible hmunity) gene product is involved in the signal transduction cascade leading to both systemic acquired resistance (SAR) and gene-for-gene disease resistance in Arabidopsis. We have isolated and characterized five new alleles of nim7 that show a range of phenotypes from weakly impaired in chemically induced pathogenesis-related protein-1 gene expression and funga1 resistance to very strongly blocked. We have isolated the NlM7 gene by using a map-based cloning procedure. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
234
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(258 citation statements)
references
References 50 publications
13
234
0
2
Order By: Relevance
“…SON1 is another F-box protein that has been implicated in plant defense signaling [58]. The son1 (suppressor of nim1-1) mutant was isolated from genetic screens for suppressors of non-inducible immunity1 (nim1, also referred as npr1), of which the corresponding wild-type gene is a key positive regulator of Arabidopsis SAR [59,60]. The son1 mutant displays SAR-independent, constitutive resistance against both the virulent oomycete Peronospora parasitica and the bacterial pathogen Pseudomonas syringae pv tomato strain DC3000, indicating that SON1-mediated ubiquitination negatively regulate plant defense.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…SON1 is another F-box protein that has been implicated in plant defense signaling [58]. The son1 (suppressor of nim1-1) mutant was isolated from genetic screens for suppressors of non-inducible immunity1 (nim1, also referred as npr1), of which the corresponding wild-type gene is a key positive regulator of Arabidopsis SAR [59,60]. The son1 mutant displays SAR-independent, constitutive resistance against both the virulent oomycete Peronospora parasitica and the bacterial pathogen Pseudomonas syringae pv tomato strain DC3000, indicating that SON1-mediated ubiquitination negatively regulate plant defense.…”
Section: Members Of the Ubiquitination System Are Implicated In Plantmentioning
confidence: 99%
“…3). Thus, the regulatory factor NPR1 (also called NIM1) 47 is not only required for the SA-dependent expression of PR genes that are activated during SAR, but also for the jasmonate-and ethylenedependent activation of so far unidentified defence responses resulting from rhizobacteria-mediated ISR.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
“…PR genes are activated in the SAR pathway but not in the ISR pathway, which suggests that the associated defence responses are differentially regulated by NPR1 depending on the signalling pathway that is activated upstream of NPR1. Sequence analysis revealed that NPR1 contains a functionally important ankyrin-repeat domain that might be involved in protein-protein interactions 47,48 . Binding of pathway-specific proteins to NPR1 might therefore account for the separation of the SAR and ISR pathways downstream of NPR1.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
“…In a genetic screening for plants failed to express PR genes after SAR induction, npr1 mutant was isolated in Arabidopsis [28] and NPR1 gene was cloned [29]. Further results revealed that NPR1 was a key regulator of SA-mediated SAR in Arabidopsis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Further results revealed that NPR1 was a key regulator of SA-mediated SAR in Arabidopsis [30][31][32]. Arabidopsis NPR1/NIM1 gene encodes a novel protein with ankyrin repeats [29], which is essential for NPR1 binding to the TGA basic leucine zipper transcription factors [33]. The interaction between NPR1 and TGA factors facilitates the binding of TGA proteins to the SA-responsive as-1 or as-1-like promoter elements, and leads to the activation of downstream genes during defense response [34,35].…”
Section: Introductionmentioning
confidence: 99%